FITOREMEDIASI AIR LIMBAH RUMAH SAKIT MENGGUNAKAN ECENG GONDOK (Eichhornia crassipes): STUDI KASUS AMONIA DAN pH - Siti Jelita Norfania Widiyawati; Rusmini (Unesa Journal of Chemistry, 2026)
Hospital wastewater contains various hazardous compounds such as ammonia (NH3) which can reduce the quality of the aquatic environment if not properly managed. Based on the results of the Hospital Wastewater Treatment Plant (WWTP) test in September 2025, the ammonia level in the effluent exceeded the quality standard of 0.26 mg/L due to damage to the aeration system (blower). This study aims to determine the effectiveness of water hyacinth (Eichhornia crassipes) in reducing ammonia levels and pH in wastewater. The study used a Quasi-Experimental design with a descriptive approach, a pretest-posttest with control group model conducted for 7 days. Most of the treated samples experienced a decrease in pH approaching neutral. The highest percentage reduction was found in sample P2 with a percentage of -7.17%. In the ammonia test, most samples experienced a decrease in ammonia levels, as shown by the change from >2 ppm at H0 to 0 ppm at H7  . This shows that water hyacinth (Eichhornia crassipes) is able to reduce ammonia levels and lower pH levels approaching neutral pH.